2019
DOI: 10.1097/mcg.0000000000000962
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Yield of 2 Strategies for Adult Celiac Disease Identification in Primary Care

Abstract: Goals:To compare the diagnostic yield and cost-consequences of 2 strategies, screening regardless of symptoms versus case finding (CF), using a point-of-care test (POCT), for the detection of celiac disease (CD) in primary care, to bridge the diagnostic gap of CD in adults. Materials and Methods:All subjects under 75 years of age who consecutively went to their general practitioners' offices were offered POCT for anti-transglutaminase immunoglobulin A antibodies. The POCT was performed on all subjects who agre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…There was a very recent study from Sicily that looked at two separate strategies for testing in primary care. 11 The first strategy involved serial testing of consecutive subjects aged <75 years being offered a point-of-care test (POCT) for coeliac disease. The second strategy involved offering only those with symptoms or associated conditions a POCT, but there was a systematic search for patients with this second strategy.…”
Section: Discussionmentioning
confidence: 99%
“…There was a very recent study from Sicily that looked at two separate strategies for testing in primary care. 11 The first strategy involved serial testing of consecutive subjects aged <75 years being offered a point-of-care test (POCT) for coeliac disease. The second strategy involved offering only those with symptoms or associated conditions a POCT, but there was a systematic search for patients with this second strategy.…”
Section: Discussionmentioning
confidence: 99%
“…One of the many studies in the past 5 years that analyzed the diagnostic yield of point-of-care tests found that the test for celiac disease has a sensitivity of 75% and a specificity of 99.2%, with a negative predictive value of 99.2% 6. The test uses IgA testing to interpret the patient's endogenous transglutaminase 2 (TG2) complexes found in the erythrocytes of whole blood by labeled antihuman IgA within 5 minutes 2.…”
Section: Diagnosismentioning
confidence: 99%
“…The increased availability and quick result time makes this test appealing and its user-friendly design encourages clinicians to begin testing for celiac disease earlier in the disease. Ultimately, the IgA point-of-care test yields increased diagnostic rates for celiac disease, which reduces the likelihood of patients developing long-term complications from undiagnosed disease 6…”
Section: Diagnosismentioning
confidence: 99%
“…This paper has been partially supported by the ITAMA project under the international cooperation program INTERREG V-A (JS-Code C1-1. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The content of this publication does not reflect the official opinion of the European Union.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…A case study in the Netherlands Youth Health Care Centres, using a POCT to assess TGA-IgA, highlighted the fact that untreated CD has a considerable health burden on society [13]. Moreover, a preceding study had suggested that a mass screening using POCTs may be a useful and economic option for screening asymptomatic children and seems more convenient than a case finding strategy based on symptoms [14], contrary to what is observed in adults [15]. A literature review [12] showed that a critical point for using a POCT as screening tool is to define, with very narrow confidence limits, the negative predictive values of a test validated in a prospective way and to determine the reference standard to all subjects to whom a test has to be applied.…”
Section: Introductionmentioning
confidence: 99%